Boundaries of Geoheritage in the Tafilalt and Maïder Regions, an Eldorado for Palaeozoic Cephalopods - Christian Klug; Carole Naglik; Merle Greif; Amin El Fassi El Fehri; Kenneth De Baets; Dieter Korn; Wahiba Bel Haouz; Abdelouahed Lagnaoui; Alexander Pohle (Geoheritage, 2026)
Morocco is world-renowned for its spectacular fossil record, spanning (among others) long intervals of the Palaeozoic. While large vertebrates or spectacular geological features and landscapes usually receive the most attention, we discuss the extraordinarily diverse and abundant cephalopod occurrences in the eastern Anti-Atlas and their role as geoheritage. We describe five remarkable geosites with their regional context including landscapes, touristic highlights and spectacular geomorphological structures. We use a standardised approach to assess the quality of these geosites according to their scientific, educational and touristic value. Additionally, we discuss potential strategies to manage geoheritage in the eastern Anti-Atlas, considering possible sites to be developed or protected, as well as geopolitical conflicts. We also provide some information about the new legal context. Finally, we shortly discuss whether protective measures are required. Clinical trial number: not applicable.

Stimulus-Responsive Polymeric Carriers for Gene Delivery: Balancing Endosomal Escape with Nucleic Acid Release - Kenneth Hulugalla; Alexander W. Fortenberry; Dilusha J. de Silva; Thomas Werfel (Pharmaceutical Research, 2026)
Background Polymeric carriers for nucleic acid delivery must overcome two sequential intracellular barriers: escape from the endosome and release of the cargo into the cytosol. These steps are typically treated as independent design problems and optimized separately. Objective This review argues that escape and release are coupled through the same electrostatic and pH-dependent interactions, creating a fundamental tradeoff . The cationic charge that enables a polymer to destabilize endosomal membranes also tightens its grip on the nucleic acid payload, so conditions favoring escape simultaneously inhibit release. Methods We trace this tradeoff across the major strategy classes in the polymeric delivery literature, evaluating each by where and when its trigger acts relative to the escape event. We further assess the assay toolkit for measuring escape and release, and the translational variables that shift the balance in vivo . Results pH-responsive polymers tune the activation zone for membrane destabilization but cannot decouple escape from binding, since both depend on the same protonation events. Charge-shifting polymers address release more directly by programming a loss of cationic character after endosomal entry. Non-pH triggers, including disulfide, thioketal, diselenide, and esterase-responsive chemistries, off er orthogonal release mechanisms but face spatial and temporal alignment constraints. Characteristic failure modes recur: premature release, redundant triggering, and kinetic misalignment. No existing assay measures endosomal disruption and cargo release state simultaneously, and translational variables including protein corona formation, cell-type-dependent endosomal acidifi cation, and PEG shielding shift the balance in ways in vitro screening does not capture. Conclusion The tradeoff cannot be resolved by chemistry alone, meaning the responsive trigger considered in isolation. Its resolution requires coordination across spatial (architectural domain segregation), temporal (kinetic alignment of escape and release), and formulation-level (N/P ratio, PEG density, formation pH) design axes.

Determinants of Community Participation in Collective Management of Natural Resources in Sub-Saharan Africa: A Systematic Review - Alexander Omondi Imbo; Uta Wehn; Kenneth Irvine (Environmental Management, 2026)
Community participation in collective management of environmental and natural resources is increasingly of interest among the sustainable development circles and scholarly discourse. There is theoretical consensus that sustainable management of natural resources is highly reliant on effective local community participation. In practice, however, realizing broad and active participation of local communities in a manner that is economically, socially and ecologically sustainable remains inconsistent. While extensive case study research has examined the dynamics of community participation aimed at understanding the enabling factors, there remains a notable gap in systematic analyses that synthesize recurring themes across these studies. In this research, we draw on the Institutional Analysis and Development Framework as an organizing theoretical framework, to review the empirical literature on collective management of common-pool natural resources in sub-Saharan Africa, in order to collate knowledge for a clearer understanding of the underlying determinants of community participation. The findings show that: the factors influencing community participation are complex, multidimensional and intersecting; different natural resources offer different combinations of ecological, economic, and social incentives that condition perceptions of benefits and costs that drive community participation; local communities are not homogenous, and the preferences and responses of individual members depend on their distinct identities and social settings; and sound local governance is the cornerstone of community participation. These insights result in specific, locally relevant policy directions for effective community participation.

Thermophilization: Concepts, Methods, and Implications of Changes in Community Composition due to Global Warming - Kenneth J. Feeley; Evelin Iseli; Billur Bektaş; Rubén D. Manzanedo; Crystal H. McMichael; Jake M. Alexander; Janneke Hille Ris Lambers (Global Change Biology, 2026)
With global warming, many species will shift their geographic ranges coldward (i.e., towards higher latitudes and elevations) to remain within suitable thermal conditions. At the community level, these range shifts result in “thermophilization”—the increasing relative abundance of warm‐adapted (“thermophilic”) species and the concomitant decrease of cold‐adapted species over time. Quantifying rates of thermophilization provides a powerful approach to assessing responses to rising temperatures at the community level, particularly in high‐diversity systems where the detailed spatial data needed to calculate species‐level responses to warming for thousands of individual species are often unavailable. This review synthesizes our current understanding of thermophilization across terrestrial, marine, and aquatic systems. We detail the most common methods used to quantify thermophilization, primarily through the calculation of the Community Temperature Index (CTI, °C), which aggregates species' thermal affiliations into a single community‐level metric that can then be tracked through time to calculate an annualized thermophilization rate (TR, °C year −1 ). We evaluate the advantages of this approach, such as its ability to partition the contributions of underlying demographic processes (i.e., recruitment vs. growth vs. mortality, or colonization vs. extinction) and/or individual species and species groups, its flexibility in using diverse data sources like herbarium records and citizen science, and its ability to test relationships between TR and site‐specific conditions such as elevation, landcover, and anthropogenic disturbances. We also discuss some of the standing challenges and limitations of the thermophilization approach, including a lack of standardization that hinders large‐scale synthetic analyses, the challenge of propagating estimation errors from the species‐ to community‐level, and difficulties in interpreting and communicating results. We then discuss the implications of thermophilization for ecosystem stability and function, including the potential for biodiversity losses and altered ecosystem services. Finally, we highlight several important and exciting avenues for future research on climate‐driven shifts in community composition.

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Mass spectrometry monitoring of drilling operations in water-doped lunar simulant under cryogenic conditions - Roberto Aguilar Ayala; Morgan A. Crabtree; Matthew L. Hancock; Alexander Jarnot; Janine E. Captain; Julie Kleinhenz; Erin Rezich; Kris Zacny; Vincent Vendiola; Zack Mank; Kenneth C. Wright; Jaime L. Winfield; et al. (Advances in Space Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

What Drives Compliance with Rules in Community-Based Conservation? Lessons from Maasai Mara, Kenya - Alexander Omondi Imbo; Uta Wehn; Kenneth Irvine (Environmental Management, 2026)

Digging Into the General Dynamic Model: How Island Ontogeny Shifts the Evolutionary Drivers of Lineage Divergence - Brock Mashburn; Alexander G. Linan; Timothée Le Péchon; Jean Claude Sevathian; Kenneth M. Olsen; Christine E. Edwards (Journal of Biogeography, 2026)
Aim The general dynamic model (GDM) of oceanic island biogeography proposes that evolutionary processes shift predictably with island ontogeny: opportunities for ecological speciation on young islands drive a rapid increase in diversity, which peaks on middle‐aged islands, then declines on older islands as extinction increases. Most studies reporting support for the GDM have not assessed the evolutionary processes associated with these phases: ecological speciation on young islands, genetic drift within species on middle‐aged islands, and finally, extinction on old islands. Here, we refine and extend the GDM by developing a set of testable predictions to show that the dominant evolutionary drivers of lineage divergence shift as islands progress through successive ontogenetic stages. We then assess whether patterns of genomic divergence are consistent with our predictions in an iconic flowering plant radiation. Location The Mascarene archipelago (Rodrigues, Mauritius, Réunion) in the Indian Ocean. Taxon Hibiscus section Lilibiscus (Malvaceae). Methods Using genome‐wide data from 2bRAD sequencing, we conducted phylogenomic, population genomic and demographic analyses (approximate Bayesian computation in DIY‐ABC) of six single‐island endemic species sampled across the three islands. Results On the youngest island, we detected signatures of ecological differentiation and high intraspecific gene flow, suggesting ecological speciation as the dominant driver of lineage divergence. On the middle‐aged island, we found that recent population structure was shaped predominantly by genetic drift, with some evidence of ancient interspecific gene flow. On the oldest island, phylogenetic and population genetic patterns were consistent with lineage loss and increased phylogenetic distance, suggesting extinction as the dominant evolutionary force. Main Conclusions Our findings provide rare empirical support for the GDM's process‐based predictions and offer a general framework for linking geomorphological change on oceanic islands to evolutionary dynamics in island systems. Our framework lays the groundwork for future population genetic studies to directly test the evolutionary processes shaping insular biodiversity.

Chemical components of electric vehicle and internal combustion engine vehicle fire smoke and their mutagenic effects - Yong Ho Kim; Adam Nored; Gavin P. Horn; Richard M. Kesler; Adam Barowy; Alex Schraiber; Benjamin Gaudet; Alexander C. Mayer; Micah Niemeier-Walsh; Kenneth W. Fent; Kasey Kovalcik; Joseph Patrick Pancras; et al. (Environmental Science and Pollution Research, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

E-cigarettes increase the risk of adenoma formation in murine colorectal cancer model - Ibrahim M. Sayed; Anirban Chakraborty; Kaili Inouye; Leanne Dugan; Stefania Tocci; Ira Advani; Kenneth Park; Samvel Gaboyan; Nikita Kasaraneni; Benjamin Ma; Tapas K. Hazra; Soumita Das; et al. (Archives of Toxicology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Advancing drinking water safety: Facile fabrication of nanofiltration membrane for enhanced antibiotics removal and efficient water softening - Yanyan Liu; Xi Zhang; Mingshuo Chi; Hideto Matsuyama; Yaoli Guo; Kenneth Simoens; Alexander Volodine; Raf Dewil; Junfeng Zheng; Zhongde Dai; Bart Van der Bruggen (Desalination, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Tarda and Tagish Lake: Samples from the same outer Solar System asteroid and implications for D- and P-type asteroids - Devin L. Schrader; Edward A. Cloutis; Daniel M. Applin; Jemma Davidson; Zachary A. Torrano; Dionysis Foustoukos; Conel M. O'D. Alexander; Kenneth J. Domanik; Moe Matsuoka; Tomoki Nakamura; Thomas J. Zega; Gregory A. Brennecka; et al. (Geochimica et Cosmochimica Acta, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Wildfire smoke impacts lake ecosystems - Mary Jade Farruggia; Janice Brahney; Andrew J. Tanentzap; Jennifer A. Brentrup; Ludmila S. Brighenti; Sudeep Chandra; Alicia Cortés; Rocio L. Fernandez; Janet M. Fischer; Alexander L. Forrest; Yufang Jin; Kenneth Larrieu; et al. (Global Change Biology, 2024)
Wildfire activity is increasing globally. The resulting smoke plumes can travel hundreds to thousands of kilometers, reflecting or scattering sunlight and depositing particles within ecosystems. Several key physical, chemical, and biological processes in lakes are controlled by factors affected by smoke. The spatial and temporal scales of lake exposure to smoke are extensive and under‐recognized. We introduce the concept of the lake smoke‐day, or the number of days any given lake is exposed to smoke in any given fire season, and quantify the total lake smoke‐day exposure in North America from 2019 to 2021. Because smoke can be transported at continental to intercontinental scales, even regions that may not typically experience direct burning of landscapes by wildfire are at risk of smoke exposure. We found that 99.3% of North America was covered by smoke, affecting a total of 1,333,687 lakes ≥10 ha. An incredible 98.9% of lakes experienced at least 10 smoke‐days a year, with 89.6% of lakes receiving over 30 lake smoke‐days, and lakes in some regions experiencing up to 4 months of cumulative smoke‐days. Herein we review the mechanisms through which smoke and ash can affect lakes by altering the amount and spectral composition of incoming solar radiation and depositing carbon, nutrients, or toxic compounds that could alter chemical conditions and impact biota. We develop a conceptual framework that synthesizes known and theoretical impacts of smoke on lakes to guide future research. Finally, we identify emerging research priorities that can help us better understand how lakes will be affected by smoke as wildfire activity increases due to climate change and other anthropogenic activities.

Shifting groundwater fluxes in bedrock fractures: Evidence from stream water radon and water isotopes - Keira Johnson; John N. Christensen; W. Payton Gardner; Matthias Sprenger; Li Li; Kenneth H. Williams; Rosemary W.H. Carroll; Nicholas Thiros; Wendy Brown; Curtis Beutler; Alexander Newman; Pamela L. Sullivan (Journal of Hydrology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Multidecadal pre- and post-collapse dynamics of the northern Larsen Ice Shelf - Shujie Wang; Hongxing Liu; Richard B. Alley; Kenneth Jezek; Patrick Alexander; Karen E. Alley; Zhengrui Huang; Lei Wang (Earth and Planetary Science Letters, 2023)

Electro-geohydraulic estimation of shallow aquifer characteristics of Njaba and environs, Southeastern Nigeria - Obinna Chigoziem Akakuru; Uzochi Bright Onyeanwuna; Alexander Iheanyichukwu Opara; Kenneth Obinna Iheme; Adora Olivia Njoku; Chinyere C. Amadi; Casmir Zander Akaolisa; Ogechi R. Okwuosha (Arabian Journal of Geosciences, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Microbial communities and processes in biofilters for post-treatment of ozonated wastewater treatment plant effluent - Daniel Sauter; Andrea Steuer; Kenneth Wasmund; Bela Hausmann; Ulrich Szewzyk; Alexander Sperlich; Regina Gnirss; Myriel Cooper; Thomas Wintgens (Science of The Total Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The decreased PG content of pgp1 inhibits PSI photochemistry and limits reaction center and light-harvesting polypeptide accumulation in response to cold acclimation - Alexander G. Ivanov; Marianna Krol; Leonid V. Savitch; Beth Szyszka-Mroz; Jessica Roche; D. P. Sprott; Eva Selstam; Kenneth W. Wilson; Richard Gardiner; Gunnar Öquist; Vaughan M. Hurry; Norman P. A. Hüner (Planta, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

Projected Shifts in 21st Century Sardine Distribution and Catch in the California Current - Jerome Fiechter; Mercedes Pozo Buil; Michael G. Jacox; Michael A. Alexander; Kenneth A. Rose (Frontiers in Marine Science, 2021)
Predicting changes in the abundance and distribution of small pelagic fish species in response to anthropogenic climate forcing is of paramount importance due to the ecological and socioeconomic importance of these species, especially in eastern boundary current upwelling regions. Coastal upwelling systems are notorious for the wide range of spatial (from local to basin) and temporal (from days to decades) scales influencing their physical and biogeochemical environments and, thus, forage fish habitat. Bridging those scales can be achieved by using high-resolution regional models that integrate global climate forcing downscaled from coarser resolution earth system models. Here, “end-to-end” projections for 21st century sardine population dynamics and catch in the California Current system (CCS) are generated by coupling three dynamically downscaled earth system model solutions to an individual-based fish model and an agent-based fishing fleet model. Simulated sardine population biomass during 2000–2100 exhibits primarily low-frequency (decadal) variability, and a progressive poleward shift driven by thermal habitat preference. The magnitude of poleward displacement varies noticeably under lower and higher warming conditions (500 and 800 km, respectively). Following the redistribution of the sardine population, catch is projected to increase by 50–70% in the northern CCS and decrease by 30–70% in the southern and central CCS. However, the late-century increase in sardine abundance (and hence, catch) in the northern CCS exhibits a large ensemble spread and is not statistically identical across the three downscaled projections. Overall, the results illustrate the benefit of using dynamical downscaling from multiple earth system models as input to high-resolution regional end-to-end (“physics to fish”) models for projecting population responses of higher trophic organisms to global climate change.

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Evaluation of engineered sorbents for the sorption of mercury from contaminated bank soils: a column study - Leroy Goñez-Rodríguez; Alexander Johs; Kenneth A. Lowe; Kimberly E. Carter; Frank E. Löffler; Melanie A. Mayes (Environmental Science and Pollution Research, 2021)
As a global environmental pollutant, mercury (Hg) threatens our water resources and presents a substantial risk to human health. The rate and extent of immobilization of Hg 2+ (hereafter, Hg) on engineered sorbents (Thiol-SAMMS®, pine biochar, SediMite™, Organoclay™ PM-199, and quartz sand as a control) was evaluated using flow-through column experiments. The effectiveness of the sorbents was based on (1) the percentage of Hg removed in relation to the total amount of Hg passing the sorbent column, and (2) the rate of Hg uptake compared to the nonreactive tracer bromide (Br − ). All sorbents removed Hg to a certain extent, but none of the sorbents removed all the Hg introduced to the columns. Thiol-SAMMS showed the highest mean percentage of Hg removed (87% ± 2.9%), followed by Organoclay PM-199 (71% ± 0.4%), pine biochar (57% ± 22.3%), SediMite (61% ± 0.8%), and the control quartz sand (11% ± 5.6%). Thiol-SAMMS was the only sorbent to exhibit retardation of Hg in comparison to the conservative tracer Br − . For the remaining sorbents, Br − along with low concentrations of Hg were eluted within the first 3 pore volumes, indicating limited retardation of Hg. Overall, removal of Hg by sorbents was substantial, suggesting that sorbents might be suitable for deployment in contaminated environments. High concentrations of DOM leaching from the soil columns likely influenced the speciation of Hg and inhibited sorption to the sorbents. Incomplete removal of Hg by any sorbent suggests that additional optimization is needed to increase efficiency.

Host-specific and tissue-dependent orchestration of microbiome community structure in traditional rice paddy ecosystems - Weijuan Huang; Sarah Gilbert; Alexander Poulev; Kenneth Acosta; Sarah Lebeis; Chunlin Long; Eric Lam (Plant and Soil, 2020)
Background and aim Rice and duckweed are two monocotyledonous plants that naturally coexist in paddy fields. While the presence of duckweed in paddy fields significantly improves rice productivity, the interplay between soil microbes and the two plant hosts in this agroecosystem remains unexplored. Methods We compared the bacterial community structure between duckweed, rice and soil from multiple rice paddies. We also isolated bacteria from these communities and characterized their modes of bacterial colonization and plant growth-promotion using model plants. Results Our data indicate that host-specific and tissue-dependent factors reproducibly orchestrate the bacterial community structure associated with their plant hosts. This is corroborated by results from culture-dependent approaches in which the dominant genus Pantoea isolated from rice aerial tissues can strongly attach and colonize gnotobiotic duckweed in spite of the low representation of this bacterial genus in the natural duckweed microbiome. Our study identified a core of 254 bacterial taxa that are consistently found in all rice and duckweed tissue samples from rice paddy fields. Furthermore, characterizing auxin-producing bacteria isolates from both plant species identified potential plant growth-promoting bacteria that may improve growth for both duckweed and rice in paddy fields. Conclusions Results from this work provide evidence for the importance of the host tissue and species context in determining plant colonization by microbes in the paddy field system. The resources generated in this study could facilitate the agronomic deployment of microbes for more sustainable rice production.

Antiproliferative activity of naphthoquinones and indane carboxylic acids from lapachol against a panel of human cancer cell lines - Kenneth O. Eyong; Herve L. Ketsemen; Zhenze Zhao; Liqin Du; Aude Ingels; Veronique Mathieu; Alexander Kornienko; Kenneth G. Hull; Gabriel N. Folefoc; Sundarababu Baskaran; Daniel Romo (Medicinal Chemistry Research, 2020)

Age matters: older age as a risk factor for CMV reactivation in the CMV serostatus–positive kidney transplant recipient - Marion Hemmersbach-Miller; Barbara D. Alexander; Carl F. Pieper; Kenneth E. Schmader (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nanodelivery of phytobioactive compounds for treating aging-associated disorders - Oleh Lushchak; Olha Strilbytska; Alexander Koliada; Alina Zayachkivska; Nadia Burdyliuk; Ihor Yurkevych; Kenneth B. Storey; Alexander Vaiserman (GeroScience, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Ocean FAIR Data Services - Toste Tanhua; Sylvie Pouliquen; Jessica Hausman; Kevin O’Brien; Pip Bricher; Taco de Bruin; Justin J. H. Buck; Eugene F. Burger; Thierry Carval; Kenneth S. Casey; Steve Diggs; Alessandra Giorgetti; et al. (Frontiers in Marine Science, 2019)

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Metformin as a geroprotector: experimental and clinical evidence - Veronika Piskovatska; Nadiya Stefanyshyn; Kenneth B. Storey; Alexander M. Vaiserman; Oleh Lushchak (Biogerontology, 2019)

Single-center analysis of infectious complications in older adults during the first year after kidney transplantation - Marion Hemmersbach-Miller; Barbara D. Alexander; Debra L. Sudan; Carl Pieper; Kenneth E. Schmader (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Changes in long‐term water quality of Baltimore streams are associated with both gray and green infrastructure - Alexander J. Reisinger; Ellen Woytowitz; Emily Majcher; Emma J. Rosi; Kenneth T. Belt; Jonathan M. Duncan; Sujay S. Kaushal; Peter M. Groffman (Limnology and Oceanography, 2019)
The steadily rising global urban population has placed substantial strain on urban water quality, and this strain is projected to increase for the foreseeable future. Considerable attention has been given to the hydrological and physico‐chemical effects of urbanization on stream ecosystems. However, due to the relative infancy of the field of urban ecology, long‐term water quality analyses in urban streams are sparse. Using a 15‐yr stream chemistry monitoring record from Baltimore, Maryland, we quantified long‐term trends in nitrate, phosphate, total nitrogen, total phosphorus, chloride, and sulfate export at several sites along a rural–urban gradient. We found no significant change in solute export at most sites, although we did find specific patterns of interest for certain solutes. For example, nitrogen export declined at the most headwater urban site, while phosphorus export declined at the most downstream urban site. Coupling long‐term monitoring with data on gray and green infrastructure management throughout the landscape, we established relationships between solute export at the most downstream urban monitoring site and sanitary sewer overflows (SSOs), best management practice (BMP) implementation, and road salt application rates. Phosphorus export was correlated with BMP implementation in the watershed, whereas nitrogen export was related to SSOs. Despite highly urbanized watersheds, water quality does not appear to be declining at most of these sites, suggesting that current management may have limited further impairment. Results of our study suggest that both gray and green infrastructure are key for maintaining and improving water quality in this highly urbanized watershed.

Methamphetamine Induces Apoptosis of Microglia via the Intrinsic Mitochondrial-Dependent Pathway - Anna V. Sharikova; Elizabeth Quaye; Jun Yong Park; Maxwell C. Maloney; Habben Desta; Ramkumar Thiyagarajan; Kenneth L. Seldeen; Neil U. Parikh; Parteet Sandhu; Alexander Khmaladze; Bruce R. Troen; Stanley A. Schwartz; et al. (Journal of Neuroimmune Pharmacology, 2018)

Considerations for the Use of Polysorbates in Biopharmaceuticals - Michael T. Jones; Hanns-Christian Mahler; Sandeep Yadav; Dilbir Bindra; Vincent Corvari; R. Matthew Fesinmeyer; Kapil Gupta; Alexander M. Harmon; Kenneth D. Hinds; Atanas Koulov; Wei Liu; Kevin Maloney; et al. (Pharmaceutical Research, 2018)

Bacterial interactions during sequential degradation of cyanobacterial necromass in a sulfidic arctic marine sediment - Albert L. Müller; Claus Pelikan; Julia R. de Rezende; Kenneth Wasmund; Martina Putz; Clemens Glombitza; Kasper U. Kjeldsen; Bo Barker Jørgensen; Alexander Loy (Environmental Microbiology, 2018)
Summary Seafloor microorganisms impact global carbon cycling by mineralizing vast quantities of organic matter (OM) from pelagic primary production, which is predicted to increase in the Arctic because of diminishing sea ice cover. We studied microbial interspecies‐carbon‐flow during anaerobic OM degradation in arctic marine sediment using stable isotope probing. We supplemented sediment incubations with 13 C‐labeled cyanobacterial necromass (spirulina), mimicking fresh OM input, or acetate, an important OM degradation intermediate and monitored sulfate reduction rates and concentrations of volatile fatty acids (VFAs) during substrate degradation. Sequential 16S rRNA gene and transcript amplicon sequencing and fluorescence in situ hybridization combined with Raman microspectroscopy revealed that only few bacterial species were the main degraders of 13 C‐spirulina necromass. Psychrilyobacter, Psychromonas, Marinifilum, Colwellia, Marinilabiaceae and Clostridiales species were likely involved in the primary hydrolysis and fermentation of spirulina. VFAs, mainly acetate, produced from spirulina degradation were mineralized by sulfate‐reducing bacteria and an Arcobacter species. Cellular activity of Desulfobacteraceae and Desulfobulbaceae species during acetoclastic sulfate reduction was largely decoupled from relative 16S rRNA gene abundance shifts. Our findings provide new insights into the identities and physiological constraints that determine the population dynamics of key microorganisms during complex OM degradation in arctic marine sediments.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd

Site-Specific Assessments of the Abundance of Three Inshore Dolphin Species to Inform Conservation and Management - Alexander M. Brown; Lars Bejder; Kenneth H. Pollock; Simon J. Allen (Frontiers in Marine Science, 2016)

Puzzling role of genetic risk factors in human longevity: “risk alleles” as pro-longevity variants - Svetlana Ukraintseva; Anatoliy Yashin; Konstantin Arbeev; Alexander Kulminski; Igor Akushevich; Deqing Wu; Gaurang Joshi; Kenneth C. Land; Eric Stallard (Biogerontology, 2016)
Complex diseases are major contributors to human mortality in old age. Paradoxically, many genetic variants that have been associated with increased risks of such diseases are found in genomes of long-lived people, and do not seem to compromise longevity. Here we argue that trade-off-like and conditional effects of genes can play central role in this phenomenon and in determining longevity. Such effects may occur as result of: (i) antagonistic influence of gene on the development of different health disorders; (ii) change in the effect of gene on vulnerability to death with age (especially, from “bad” to “good”); (iii) gene–gene interaction; and (iv) gene–environment interaction, among other factors. A review of current knowledge provides many examples of genetic factors that may increase the risk of one disease but reduce chances of developing another serious health condition, or improve survival from it. Factors that may increase risk of a major disease but attenuate manifestation of physical senescence are also discussed. Overall, available evidence suggests that the influence of a genetic variant on longevity may be negative, neutral or positive, depending on a delicate balance of the detrimental and beneficial effects of such variant on multiple health and aging related traits. This balance may change with age, internal and external environments, and depend on genetic surrounding. We conclude that trade-off-like and conditional genetic effects are very common and may result in situations when a disease “risk allele” can also be a pro-longevity variant, depending on context. We emphasize importance of considering such effects in both aging research and disease prevention.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Quorum sensing activity and control of yeast-mycelium dimorphism in Ophiostoma floccosum - Alexander Berrocal; Claudia Oviedo; Kenneth W. Nickerson; José Navarrete (Biotechnology Letters, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Recommendations for a national agenda to substantially reduce cervical cancer - Jennifer S. Smith; Noel T. Brewer; Debbie Saslow; Kenneth Alexander; Mildred R. Chernofsky; Richard Crosby; Libby Derting; Leah Devlin; Charles J. Dunton; Jeffrey Engle; Maria Fernandez; Mona Fouad; et al. (Cancer Causes & Control, 2013)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Effect of Superphosphate and Arbuscular Mycorrhizal Fungus Glomus mosseae on Phosphorus and Arsenic Uptake in Lentil (Lens culinaris L.) - Fazel R. Sadeque Ahmed; Ian J. Alexander; Mwinyikione Mwinyihija; Kenneth Killham (Water, Air, & Soil Pollution, 2011)

Pulmonary Gene Silencing in Transgenic EGFP Mice Using Aerosolised Chitosan/siRNA Nanoparticles - Ebbe J. B. Nielsen; Jan M. Nielsen; Daniel Becker; Alexander Karlas; Hridayesh Prakash; Sys Z. Glud; Jonathan Merrison; Flemming Besenbacher; Thomas F. Meyer; Jørgen Kjems; Kenneth A. Howard (Pharmaceutical Research, 2010)

Spatial distribution and temporal dynamics of high‐elevation forest stands in southern Siberia - Vyacheslav I. Kharuk; Kenneth J. Ranson; Sergey T. Im; Alexander S. Vdovin (Global Ecology and Biogeography, 2010)
Aim To evaluate the hypothesis that topographic features of high‐elevation mountain environments govern spatial distribution and climate‐driven dynamics of the forest. Location Upper mountain forest stands (elevation range 1800–2600 m) in the mountains of southern Siberia. Methods Archive maps, satellite and on‐ground data from1960 to 2002 were used. Data were normalized to avoid bias caused by uneven distribution of topographic features (elevation, azimuth and slope steepness) within the analysed area. Spatial distribution of forest stands was analysed with respect to topography based on a digital elevation model (DEM). Results Spatial patterns in mountain forests are anisotropic with respect to azimuth, slope steepness and elevation. At a given elevation, the majority of forests occupied slopes with greater than mean slope values. As the elevation increased, forests shifted to steeper slopes. The orientation of forest azimuth distribution changed clockwise with increase in elevation (the total shift was 120°), indicating a combined effect of wind and water stress on the observed forest patterns. Warming caused changes in the forest distribution patterns during the last four decades. The area of closed forests increased 1.5 times, which was attributed to increased stand density and tree migration. The migration rate was 1.5 ± 0.9 m year –1 , causing a mean forest line shift of 63 ± 37 m. Along with upward migration, downward tree migration onto hill slopes was observed. Changes in tree morphology were also noted as widespread transformation of the prostrate forms of Siberian pine and larch into erect forms. Main conclusions The spatial pattern of upper mountain forests as well as the response of forests to warming strongly depends on topographic relief features (elevation, azimuth and slope steepness). With elevation increase (and thus a harsher environment) forests shifted to steep wind‐protected slopes. A considerable increase in the stand area and increased elevation of the upper forest line was observed coincident with the climate warming that was observed. Warming promotes migration of trees to areas that are less protected from winter desiccation and snow abrasion (i.e. areas with lower values of slope steepness). Climate‐induced forest response has significantly modified the spatial patterns of high‐elevation forests in southern Siberia during the last four decades, as well as tree morphology.

Effects of pulsed riverine versus non-pulsed wastewater inputs of freshwater on plant community structure in a semi-arid salt marsh - Margaret G. Forbes; Heather D. Alexander; Kenneth H. Dunton (Wetlands, 2008)

Wolbachia endobacteria depletion by doxycycline as antifilarial therapy has macrofilaricidal activity in onchocerciasis: a randomized placebo-controlled study - Achim Hoerauf; Sabine Specht; Marcelle Büttner; Kenneth Pfarr; Sabine Mand; Rolf Fimmers; Yeboah Marfo-Debrekyei; Peter Konadu; Alexander Yaw Debrah; Claudio Bandi; Norbert Brattig; Anna Albers; et al. (Medical Microbiology and Immunology, 2008)

Wolbachia endobacteria depletion by doxycycline as antifilarial therapy has macrofilaricidal activity in onchocerciasis: a randomized placebo-controlled study - Achim Hoerauf; Sabine Specht; Marcelle Büttner; Kenneth Pfarr; Sabine Mand; Rolf Fimmers; Yeboah Marfo-Debrekyei; Peter Konadu; Alexander Yaw Debrah; Claudio Bandi; Norbert Brattig; Anna Albers; et al. (Medical Microbiology and Immunology, 2008)

Climate, stream flow prediction and water management in northeast Brazil: societal trends and forecast value - Kenneth Broad; Alexander Pfaff; Renzo Taddei; A. Sankarasubramanian; Upmanu Lall; Franciso de Assis de Souza Filho (Climatic Change, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Sources of Insect and Plant Volatiles Attractive to Cottonwood Leaf Beetles Feeding on Hybrid Poplar - Alexander P. Kendrick; Kenneth F. Raffa (Journal of Chemical Ecology, 2006)

Adaptive Management of the Global Climate Problem: Bridging the Gap Between Climate Research and Climate Policy - Joseph Arvai; Gavin Bridge; Nives Dolsak; Robert Franzese; Tomas Koontz; April Luginbuhl; Paul Robbins; Kenneth Richards; Katrina Smith Korfmacher; Brent Sohngen; James Tansey; Alexander Thompson (Climatic Change, 2006)

Novel hydrolase diversity retrieved from a metagenome library of bovine rumen microflora - Manuel Ferrer; Olga V. Golyshina; Tatyana N. Chernikova; Amit N. Khachane; Dolores Reyes‐Duarte; Vitor A. P. Martins Dos Santos; Carsten Strompl; Kieran Elborough; Graeme Jarvis; Alexander Neef; Michail M. Yakimov; Kenneth N. Timmis; et al. (Environmental Microbiology, 2005)
Summary A metagenome expression library of bulk DNA extracted from the rumen content of a dairy cow was established in a phage lambda vector and activity‐based screening employed to explore the functional diversity of the microbial flora. Twenty‐two clones specifying distinct hydrolytic activities (12 esterases, nine endo‐β‐1,4‐glucanases and one cyclodextrinase) were identified in the library and characterized. Sequence analysis of the retrieved enzymes revealed that eight (36%) were entirely new and formed deep‐branched phylogenetic lineages with no close relatives among known ester‐ and glycosyl‐hydrolases. Bioinformatic analyses of the hydrolase gene sequences, and the sequences and contexts of neighbouring genes, suggested tentative phylogenetic assignments of the rumen organisms producing the retrieved enzymes. The phylogenetic novelty of the hydrolases suggests that some of them may have potential for new applications in biocatalysis.

Doxycycline as a novel strategy against bancroftian filariasis?depletion of Wolbachia endosymbionts from Wuchereria bancrofti and stop of microfilaria production - Achim Hoerauf; Sabine Mand; Kerstin Fischer; Thomas Kruppa; Yeboah Marfo-Debrekyei; Alexander Yaw Debrah; Kenneth M. Pfarr; Ohene Adjei; Dietrich W. Bttner (Medical Microbiology and Immunology, 2003)

Effects of lorazepam and oxazepam on perceptual and procedural memory functions - Janine Martin; Allison Matthews; Frances Martin; Kenneth Kirkby; James Alexander; Brett Daniels (Psychopharmacology, 2002)

Effective and Equitable Dissemination of Seasonal-to-Interannual Climate Forecasts: Policy Implications from the Peruvian Fishery during El Niño 1997–98 - Kenneth Broad; Alexander S. P. Pfaff; Michael H. Glantz (Climatic Change, 2002)

Perceptual variation in categorizing individual peripheral joints for the presence or absence of osteoarthritis using a standard homunculus: observations based on an australian twin registry study of osteoarthritis - Nicholas Bellamy; Alexander Klestov; Kenneth Muirden; Petra Kuhnert; Kim-Anh Do; Louise O’gorman; Nicholas Martin (Inflammopharmacology, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Informational analysis of left-ventricle/systemic-arterial interaction - Kenneth B. Campbell; John A. Ringo; Chalapathy Neti; John E. Alexander (Annals of Biomedical Engineering, 1984)